2018
DOI: 10.1039/c7cp07890k
|View full text |Cite
|
Sign up to set email alerts
|

Noble gas encapsulated B40cage

Abstract: The efficacy of B borospherene to act as a host for noble gas atoms is explored via density functional theory based computations. Although the Ng@B complexes are thermochemically unstable with respect to dissociation into free Ng and B, it does not rule out their viability as all the systems possess a high activation free energy barrier (84.7-206.3 kcal mol). Therefore, once they are formed, it is hard to take out the Ng atom. Two Ng atoms can also be incorporated within B for the lighter Ng atoms (He and Ne).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 94 publications
2
18
0
Order By: Relevance
“…The ab initio MD study on Ng 2 @C 60 showed that Ng 2 units, including He 2 , undergo translational, vibrational, and rotational movements as a single entity, without any random movement, supporting some sort of bonding between two He atoms. 57 A similar situation was noted in Ng 2 conned in a smaller cavity like B 12 N 12 , B 16 N 16 , and B 40 cages 106,107 where some specic descriptors support bonding and some criteria do not. Therefore, it is only a matter of weightage an individual wants to give.…”
supporting
confidence: 68%
“…The ab initio MD study on Ng 2 @C 60 showed that Ng 2 units, including He 2 , undergo translational, vibrational, and rotational movements as a single entity, without any random movement, supporting some sort of bonding between two He atoms. 57 A similar situation was noted in Ng 2 conned in a smaller cavity like B 12 N 12 , B 16 N 16 , and B 40 cages 106,107 where some specic descriptors support bonding and some criteria do not. Therefore, it is only a matter of weightage an individual wants to give.…”
supporting
confidence: 68%
“…Borospherene (B 40 ) can also encapsulate Ng atoms and systems like Ng n @B 40 (n = 1 for He-Rn; n = 2 for He-Kr) [140] have been studied using DFT methods. The systems are not thermodynamically stable with respect to the dissociation to B 40 cage and free Ng atoms, but once the entrapped cages are formed, they are kinetically stable due to a high free energy barrier (Δ G ‡ ).…”
Section: Discussionmentioning
confidence: 99%
“…Cerpa et al ( 2009 ) have studied the effect of confinement on the electronic interaction between He-He bond in the host C 20 H 20 and their results followed that a shorter He-He bond does not always indicate a chemical bond. Not only are the carbon related compounds considered as the hosts for entrapping the Ng atoms and their dimers, but hosts constituted with other elements such as B 40 cage (Pan et al, 2018 ), B 12 N 12 (Khatua et al, 2014a ; Paul et al, 2019 ), B 16 N 16 (Khatua et al, 2014a ), , and (Sekhar et al, 2017 ) are also reported. Encapsulation of Ng and Ng 2 in B 12 N 12 and B 16 N 16 fullerenes show that the dimer He 2 undergoes not only vibration and translation, but also rotation inside the cage.…”
Section: Introductionmentioning
confidence: 99%